L. WONG - Adaptive Reuse. Extending the Lives of Buildings - Gioeni, Laura (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2021)
Liliane Wong Adaptive Reuse. Extending the Lives of Buildings Basilea: Birkhäuser, 2016. 264 pp. Softcover. Language: English. 39,95 € ISBN: 978-3038215370